2014
DOI: 10.1371/journal.pone.0099220
|View full text |Cite
|
Sign up to set email alerts
|

An Active Poroelastic Model for Mechanochemical Patterns in Protoplasmic Droplets of Physarum polycephalum

Abstract: Motivated by recent experimental studies, we derive and analyze a two-dimensional model for the contraction patterns observed in protoplasmic droplets of Physarum polycephalum. The model couples a description of an active poroelastic two-phase medium with equations describing the spatiotemporal dynamics of the intracellular free calcium concentration. The poroelastic medium is assumed to consist of an active viscoelastic solid representing the cytoskeleton and a viscous fluid describing the cytosol. The equati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 61 publications
4
80
1
Order By: Relevance
“…Indeed, it is unclear how Physarum exerts stresses on its surroundings. Previous models have suggested that wave-like patterns of contraction may spontaneously arise from the coupling of the mechanics and chemistry of contraction in Physarum [20,21]. It is plausible that a similar mechanism may give rise to a wave-like modulation of the strength of adhesive interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it is unclear how Physarum exerts stresses on its surroundings. Previous models have suggested that wave-like patterns of contraction may spontaneously arise from the coupling of the mechanics and chemistry of contraction in Physarum [20,21]. It is plausible that a similar mechanism may give rise to a wave-like modulation of the strength of adhesive interactions.…”
Section: Discussionmentioning
confidence: 97%
“…In two-phase models of the cytoplasm suggested to model the dynamics of Physarum polycephalum the dynamics of the fluid viscous cytosol is taken into account in addition to the dynamics of the active solid viscoelastic cytoskeleton described by a Kelvin-Voigt model [20,21,23]. The resulting model equations are, however, apart from the sign of the active stress identical to the one-phase Kelvin-Voigt model given above and therefore, present, the best choice for modeling Physarum as an active solid.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Radszuweit et al [20] showed that the whole variety of deformations pattern observed in experiments with plasmodial droplets of Physarum polycephalum reported in [8,9,10,11] require also an extension of the active poroelastic model by reactiondiffusion equations describing the regulation of calcium ions. …”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of Physarum cells as being poroelastic media was used previously in a series of studies aiming at understanding the dynamics of the reorganization of protoplasmic droplets and the related deformation patterns [3,44,45].…”
Section: Introductionmentioning
confidence: 99%